Modelado del THD en los sistemas de iluminación de inducción residenciales - Bedoya Ayora, Luis Fernando (2015)
In this thesis presents a modeling project is developed to study the behavior and the effects on the electrical distribution network can be presented by the presence of harmonics generated by induction lamps for residential use; the mathematical model of induction lamp with external inductor is first obtained and then make modeling using MATLAB and the same mathematical tool calculate the rate of total harmonic distortion produced by these lamps and the graph of harmonics and distortion is obtained waveform; with the data provided by the characteristic curve of demand peaks are achieved display in the hours of greatest stress.